Atypicalities of Gesture Form and Function in Autistic Adults. - de Marchena, A.; Kim, E. S.; Bagdasarov, A.; Parish-Morris, J.; Schultz, R. T.; Maddox, B. B.; Brodkin, E. S. (Journal of Autism & Developmental Disorders, 2019)
While well-represented on clinical measures, co-speech gesture production has never been formally studied in autistic adults. Twenty-one verbally fluent autistic adults and 21 typically developing controls engaged in a controlled conversational task. Group differences were observed in both semantic/pragmatic and motoric features of spontaneously produced co-speech gestures. Autistic adults prioritized different functions of co-speech gesture. Specifically, they used gesture more than controls to facilitate conversational turn-taking, demonstrating a novel nonverbal strategy for regulating conversational dynamics. Autistic adults were more likely to gesture unilaterally than bilaterally, a motoric feature of gesture that was individually associated with autism symptoms. Co-speech gestures may provide a link between nonverbal communication symptoms and known differences in motor performance in autism.